A Study of Perceptions, Practices and Attitudes on Food Hygiene and Hazard Analysis Critical Control Point in The Indonesian Food Industry - Agus Sudibyo; M Maman Rohaman (Warta Industri Hasil Pertanian, 2004)
A study of perceptions ,practices and attitudes on food hygiene and hazard analysis critical control point (HACCP) in the indonesian food industry has been conducted.This study was carried out by survey an interview, plants visit and distribute a questionnaire to managers of small,medium and largefood industries at seven provinces,i.e.DKI Jakarta,West Jawa,Central of Jawa,East JawaNorth Sumatera,South Sulawesi and Bali.The number of samples for respondent for this study were 102 food businnes and they were asked about the food hygienepractices in their bussinnes their system used such as HACCP,and the perceptions and attitudes toward a range of food hygiene issues.The result showed that HACCP systems were implemented at 57%in the large food industries more than 15% and 0%in the medium and small food industry,respectively (P<0.005):58% of small,54 prevent of medium and 51%of large food industry managers thought their business represented a low-risk to food safety.Higher levels of food hygiene qualitications among the industry manager and higer perceptions among managers of the risk of food safety of the business were also significantly related to use HACCP in al sector (P<0.05).